Serendipia: Inward GAZES (ARQUISUR Revista, 2021)
These are brief and exploratory investigations, mostly fortuitous, arising from many other investigations, heterodox in their methodological nature that appeals to subjective reflection rather than to the rigor of the positivist investigation.For this reason, as reflection is the main task of this work, it is developed on the inward gazes of the researcher and writer himself, and the astonishment that these gazes provoke in him. A work of reflection, that although it starts from primary and secondary documents, is developed as a task of speculation, reasoning, analysis and free elaboration of a basic material, it is not necessary abundant or extensive. As in all researchs, sources are also used that, although they are not mentioned, affect the execution of the article, sources that interweave a substrate of remembered images, not always with total accuracy.This work is only a fragment, a clipping of a long history of views with which the object of study is once again questioned and investigated in some way. A clipping that focuses only on some aspects that for reasons of limited length of the article must be selected from many others and synthesized.
Keywords: architecture, equipment, interior space, landscape, dwelling